AB0412 Clinical Meaningfulness of Radiographic Joint Damage on Physical Function, Employability and Work Productivity in Patients with Rheumatoid Arthritis: Results from the Intravenous Golimumab Study, Go-Further. (9th June 2015) - Han, C.; Bingham, C.O.; Westhovens, R.; Weinblatt, M.E.; Kim, L.; Baker, D.; Peterson, S.; Hsia, E.
Abstract : Objectives: To evaluate clinical meaningfulness of radiographic joint damage on physical function, employability and work productivity of patients with rheumatoid arthritis (RA). Methods: GO-FURTHER was a multicenter, randomized, placebo-controlled study. Adult patients with active RA despite MTX therapy (≥6 tender and swollen joints, CRP ≥1.0 mg/dL, and RF and/or anti-CCP positive) were randomized to placebo + MTX (PBO+MTX) or GLM (2mg/kg) plus MTX at week 0, 2, and every 8 week thereafter (GLM group). Physical function was assessed using Health Assessment Questionnaire (HAQ). Employability was defined as being employed or to be able to work if job is available. Radiographic progression was measured using the van der Heijde modified total Sharp score (mTSS). Results: At baseline, the mean (SD) mTSS was 48.5 (56.4) and 13.5% of patent had a mTSS of >100. mTSS was correlated with HAQ score (r=0.23, p<0.001); For patients who had mTSS>100, 65.8% reported severe disability (HAQ>1.5) with a mean HAQ score of 1.8, while those who had no joint damage at the baseline, 45.4% experienced severe disability with a mean HAQ of 1.2. Patients with a mTSS>100 were more likely unemployable due to RA (44.2%), compared to 11.1% for those with no joint damage. The mTSS was correlated with overall impact of disease on daily productivity. The association of greater joint damage with low employability was observed even after adjusting for HAQ scores. Conclusions: RA patients with physical disability accompanied with joint damage were more likely to have work disability and/or reduced daily productivity, indicating that effective RA management to prevent long-term joint damage is important to retain RA patients in the workforce. Disclosure of Interest: C. Han Employee of: J&J Pharmaceutical Services, LLC., C. Bingham Grant/research support from: Janssen Research & Development, LLC., R. Westhovens Grant/research support from: Janssen Research & Development, LLC., M. Weinblatt Grant/research support from: Janssen Research & Development, LLC., L. Kim Employee of: Janssen Research & Development, LLC., D. Baker Employee of: Janssen Research & Development, LLC., S. Peterson Employee of: J&J Pharmaceutical Services, LLC., E. Hsia Employee of: Janssen Research & Development, LLC.